The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1088/0264-9381/30/15/155006
|View full text |Cite
|
Sign up to set email alerts
|

Explicit harmonic and spectral analysis in Bianchi I–VII-type cosmologies

Abstract: The solvable Bianchi I-VII groups which arise as homogeneity groups in cosmological models are analyzed in a uniform manner. The dual spaces (the equivalence classes of unitary irreducible representations) of these groups are computed explicitly. It is shown how parameterizations of the dual spaces can be chosen to obtain explicit Plancherel formulas. The Laplace operator ∆ arising from an arbitrary left invariant Riemannian metric on the group is considered, and its spectrum and eigenfunctions are given expli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Although the results of the previous section are explicit (if one follows closely the details in [7,8]), they are quite complicated. In certain particular cases it might be easier to rely on some direct treatment, as [2].…”
Section: The Connected Simply Connected Solvable Bianchi Groupsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the results of the previous section are explicit (if one follows closely the details in [7,8]), they are quite complicated. In certain particular cases it might be easier to rely on some direct treatment, as [2].…”
Section: The Connected Simply Connected Solvable Bianchi Groupsmentioning
confidence: 99%
“…Then the Lie bracket is [(α, β; γ), (α ′ , β ′ ; γ ′ )] = γM (α ′ , β ′ ) − γ ′ M (α, β); 0 . From now on we shall rely on results from [2], in which the authors found easier to apply directly Mackey's induced representation theory for semidirect product than the parametrization methods of Currey. The emphasis is on the orbit structure of the contragredient action M ⊥ of R on the dual R 2 ≡ R 2 .…”
Section: The Connected Simply Connected Solvable Bianchi Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…The set of spacetimes with homogeneous Cauchy hypersurfaces encompasses the well known Bianchi spacetimes [19]. Hadamard states were recently constructed on these spacetimes by the authors of [20]. We will briefly comment on examples of spacetimes whose Cauchy hypersurfaces are compact and homogeneous.…”
Section: Introductionmentioning
confidence: 99%